A survey on multi-source heterogeneous data processing methods in manufacturing process - Shichao CHEN; Chunyu CUI; Hua ZHANG; Ge MA; Fenghua ZHU; Xiuqin SHANG; Gang XIONG (大数据)
The effective processing and deep mining analysis of data can provide manufacturers with more effective production scheduling,equipment management and other strategies to affect production yield and efficiency.The processing methods and technologies of multi-source heterogeneous data in the manufacturing process were systematically reviewed.Firstly,the multi-source heterogeneous data content and classification in the manufacturing process was clarified.Secondly,the data processing methods and techniques applied in various stages of data collection,data integration and data analysis in the multi-source heterogeneous data processing were described.And the advantages and disadvantages of various techniques and their applications were analyzed.Finally,the multi-source heterogeneous data processing methods and techniques in the manufacturing process were summarized.And the challenges and development trends were pointed out.